2011
DOI: 10.1080/13607863.2010.508773
|View full text |Cite
|
Sign up to set email alerts
|

Self-awareness of memory function in Parkinson's disease in relation to mood and symptom severity

Abstract: Self-awareness of memory function is relatively well preserved in PD, but is negatively affected by depressive symptoms. Patient-proxy discrepancies increase also with disease severity, degree of memory problems and cognitive control deficits. Caregivers seem to be unaware of the specificity of memory problems in PD and report only some of them, mainly those related to verbal recall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
72
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 26 publications
6
72
4
Order By: Relevance
“…They also showed significantly higher HADS-D scores when compared to PD-NC group. These findings may be explained by the fact that patients with depressive symptoms are likely to overestimate their cognitive symptoms 30 . This is consistent with Marino et al 12 who concluded that PD patients with memory-related complaints showed mood disorders and that there was no relationship between subjective complaints and objective cognitive impairment.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…They also showed significantly higher HADS-D scores when compared to PD-NC group. These findings may be explained by the fact that patients with depressive symptoms are likely to overestimate their cognitive symptoms 30 . This is consistent with Marino et al 12 who concluded that PD patients with memory-related complaints showed mood disorders and that there was no relationship between subjective complaints and objective cognitive impairment.…”
mentioning
confidence: 66%
“…Anosognosia is very common in patients with neurodegenerative conditions and significantly impact on function and quality of life of these patients and their caregivers 27 . According to Sitek et al 30 it is a relevant aspect for patient follow-up since, misperception of one' s own deficits in patients with PD has been associated to the development of dementia. PD-C group had similar cognitive performance as compared to the other groups studied.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the impact of dyskinesia as a key factor on QoL in PD patients has not been fully elucidated. Sitek et al [28] explained the relationship between dyskinesia and “stigmatization,” which may impact the QoL of PD patients. “Stigma” and “emotional well-being” are the significant contributors that impact the caregivers' burden.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that patients are accurate reporters of disability, even in the presence of cognitive compromise and depression [ 128 ] . In contrast, in the case of memory impairment, whereas the patient's and care partner's report is typically concordant and related to patient scores on objective cognitive measures, patient-care partner report discrepancies increase as a function of patient cognitive impairment and depression [ 129 ] . One study reported that care partners may focus on select aspects of cognitive de fi cit such as verbal recall [ 129 ] , but another study found good concordance between caregiver report and patient's objective performance on a range of cognitive tasks, including those measuring memory, executive function, language, and psychomotor speed [ 130 ] .…”
Section: Interviewmentioning
confidence: 95%
“…In contrast, in the case of memory impairment, whereas the patient's and care partner's report is typically concordant and related to patient scores on objective cognitive measures, patient-care partner report discrepancies increase as a function of patient cognitive impairment and depression [ 129 ] . One study reported that care partners may focus on select aspects of cognitive de fi cit such as verbal recall [ 129 ] , but another study found good concordance between caregiver report and patient's objective performance on a range of cognitive tasks, including those measuring memory, executive function, language, and psychomotor speed [ 130 ] . A useful observation to keep in mind is that patients, including those with PDD and DLB, may frequently complain of memory disorders initially [ 25 ] , but what patients describe as memory disorders may actually represent other de fi cits.…”
Section: Interviewmentioning
confidence: 95%